INCREASE IN EFFICIENCY OF THE CYCLIC DRIVING OF WELLS IN SOIL - V. P. Gileta; I. V. Tishchenko; Yu. V. Vanag (Вестник СибАДИ)
Processing methods of a cyclic driving of wells with a diameter over 300 mm by methods of vibro-impact pushing and combined with partial consolidation and excavation of soil on the basis of use of pneumo-percussive mashines (pneumatic bore-hole driver) are given in work. The results of researches received with use of the ground intake devices physical models have allowed to establish characteristics of change of force of resistance to the return transportation of the equipment with the taken soil core in process of his removal from a face. Analytical expressions for engineering calculation of the winch tractive force are received. Technical characteristics of the created number of the winches of scraper type working at the uniform energy carrier with shock cars – compressed air are given.The schematic diagram winch with hybrid pneumatic drive, the having variable traction and high-speed characteristic is offered at a limited expense of the energy carrier which realization of a design at vibroshock breakdown and a combined method allows to reduce time of a production cycle of formation of wells and to increase productivity of driving works. A schematic diagram of a winch with a hybrid pneumatic drive is proposed, which has variable traction and speed characteristics with a limited energy carrier consumption, the implementation of the design which in vibro-impact pushing and combined method allows to reduce time of process of formation of wells and improve the performance of the tunneling works.